Feminist sport through the Algerian visual media (Algerian TV) - from the point of view of the players of the Arab Maghreb Football Club in Djelfa Senior category - hamadi, ameur; Mohammed (sports creativity, 2025)
This study aims to know the role that sports media plays by covering sports activities of all kinds, especially women's sports. In this study, the questionnaire tool was relied upon, as it was applied to an intentional sample represented in 20 footballers in the Arab Maghreb Club in Djelfa Also, the reliance was made on the descriptive approach and on the percentages and enough squaring in this study, and the results have shown that women's sport in Algeria does not have the appropriate and necessary media coverage at various levels and degrees and which suffers from a major media deficiency